Определение изменения видового состава вирулентной микрофлоры при язвенном пульпите на этапах эндодонтического лечения (LLC "Endo Press", 2020)
The analysis of the microbial flora of root canals with chronic ulcerative pulpitis at the stage of endodontic treatment was carried out. Antibacterial and anti-inflammatory efficacy in the preparations at endodontic treatment of root canals was studied. Clinical studies of 83 patients showed that the analysis of microbial flora in the content of root canals in patients with ulcerative pulpitis allowed identifying associations of two to nine species of bacteria, which mainly referred to microaerophilic or obligate-anaerobic species. Variations of species composition of virulent microflora at the stages of endodontic treatment were established. With the use of calcium hydroxide decontamination efficacy of antibacterial root canal system increases twice, while with the use of copper-calcium hydroxide it increases four times.